Is the Value of The Company Affected by Company Investment Decisions and Financing Decisions? - Ramon Arthur Ferry Tumiwa; John Ronaldo Michael Apituley; Stevie Alan Lasut (Journal of International Conference Proceedings (JICP), 2020)
This study aims to examine and analyze whether investment and financing decisions have a significant effect on the firm value of manufacturing companies listed on the Indonesia Stock Exchange. This study uses data from food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the period 2013 to 2017. The analyzed companies are 13 companies based on sample criteria. The analysis method used is panel data analysis by using Microsoft Excel and Eviews 10 software. The results of this study found that investment decisions have a positive effect but not significant on firm value and financing decisions have a significant and positive effect on firm value in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange.